Student movements in Brazil and Mexico in 1968: comparative analysis of their demands - Donoso Romo, Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article contrasts the demands of two of the main student movements known in Latin America during the third quarter of the 20th century, those of Brazil and Mexico in 1968. This is an original task in that the investigations in this field have mainly focused only on one movement and, in addition, have prioritized the analysis of what was their most dramatic dimension: politics. This means that here, not only are both movements addressed, but also their political and educational aspects are studied in an integrated manner. In order to carry out this task, a historical methodology was employed which included a review of the main primary and secondary sources. This exercise concluded that these movements effectively constituted groups of protests against authoritarianism as well as spaces for the defense of university autonomy and the promotion of a university that was more involved in social issues.